Pengaruh Current Ratio dan Debt to Equity Ratio Terhadap Return On Asset Pada PT Charoen Pokphand Indonesia, Tbk Periode 2011 - 2020 - Aulia Qotrunnada; Tri Sulistyani (Journal of Accounting and Finance (JACFIN), 2023)
The purpose of this study is as a research tool to determine the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return On Assets (ROA) at PT Charoen Pokphand Indonesia Tbk. The research method used in this research is quantitative research and uses descriptive and associative statistical analysis. The financial statements of PT Charoen Pokphand Indonesia Tbk are the population in this study and the data from the notes to the financial statements and profit and loss statements of PT Charoen Pokphand Indonesia Tbk, for the period 2011 – 2020 is the sample using a systematic sampling technique. The results of this study indicate that, partially Current Ratio has a significant positive effect on Return On Assets with a tcount of 2,983 > ttable of 2.365 and a significant value of 0.020 <0.05. And the Debt to Equity Ratio partially does not have a significant negative effect on Return On Assets with a tcount of -1.040 < ttable 2.365 and a significant value of 0.333 > 0.05. Simultaneously Current Ratio and Debt to Equity Ratio have a significant effect on Return On Assets with Fcount 8.532 > Ftable 4.46 and a significance value of 0.013 <0.05, then H0 is rejected and Ha is accepted.